A Digital Ecosystem–Based Anticorruption Character Education Model: A Review of the Corruption Eradication Commission’s Educational Innovations through e-KPK Learning and KIRANA - Helena Christine D; Musashi Pangeran Batara; Muhammad Abid Djazul; Eka Ardi Handoko; Iwan Armawan (JKEN: Jurnal Kajian Ekonomi Nasional, 2026)
Abstract                                                                                     This study aims to analyze the role of digital ecosystem-based anti-corruption character education as a strategy for preventing corruption in Indonesia. The method used is a qualitative approach with a literature study of six national scientific journals relevant to the issues of corruption, anti-corruption education, character education, and the use of digital technology. The data were analyzed using content analysis techniques to identify concepts, findings, and the relevance of digital anti-corruption education models, particularly those developed by the Corruption Eradication Commission through the e-KPK Learning and KIRANA platforms. The results of the study show that anti-corruption character education based on a digital ecosystem is effective in increasing moral awareness, integrity, and student participation. This model is considered adaptive, sustainable, and relevant in addressing the complexity of corruption issues in Indonesia, thus having the potential to strengthen a culture of integrity in public and institutional life.   Keywords: Corruption; Character Education; Anti-Corruption Education; Digital Ecosystem; Corruption Eradication Commission